2016
DOI: 10.1128/iai.00011-15
|View full text |Cite
|
Sign up to set email alerts
|

Memory B Cells Encode Neutralizing Antibody Specific for Toxin B from the Clostridium difficile Strains VPI 10463 and NAP1/BI/027 but with Superior Neutralization of VPI 10463 Toxin B

Abstract: T he role of immune cell memory in Clostridium difficile infection (CDI) remains poorly understood. CDI is complicated by a high frequency of recurrence, often after disease has apparently resolved, and can be associated with progressively worsening pathology and ultimately death (1). However, patients that develop antibodies (Ab) capable of neutralizing two toxins secreted by C. difficile (TcdA and TcdB) are less likely to experience recurrence (reviewed in reference 2). This suggests that memory B (Bmem) cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 53 publications
5
27
1
Order By: Relevance
“…Mice were immunized at between the ages of 8 and 10 weeks with a subcutaneous injection divided between both rear flanks. Vaccines consisted of 50 g of TcdB2 D270N or TcdB2 Δ1769 -1787 in sterile PBS adsorbed to alhydrogel alum (InvivoGen, San Diego, CA) (35). The mice were initially vaccinated on day 0, followed by a booster at day 28.…”
Section: Destabilizing Internal Deletions In Tcdb2mentioning
confidence: 99%
“…Mice were immunized at between the ages of 8 and 10 weeks with a subcutaneous injection divided between both rear flanks. Vaccines consisted of 50 g of TcdB2 D270N or TcdB2 Δ1769 -1787 in sterile PBS adsorbed to alhydrogel alum (InvivoGen, San Diego, CA) (35). The mice were initially vaccinated on day 0, followed by a booster at day 28.…”
Section: Destabilizing Internal Deletions In Tcdb2mentioning
confidence: 99%
“…There could also be intrinsically different adaptive immune responses to similar Ags produced by different strains. The Lang laboratory recently reported that TcdB1 and TcdB2 were similarly immunogenic in mice, resulting in very similar Ab profiles with regard to Ig sub-class [10]. In that study, while long-term memory B-cell driven Ab recall responses were observed against TcdB1 and TcdB2, neutralization of TcdB2 and resistance to in vivo challenge with toxin was vastly inferior to that against TcdB1 [10].…”
Section: Vaccine Candidates and Constraints On Adaptive Immunity To Themmentioning
confidence: 99%
“…The Lang laboratory recently reported that TcdB1 and TcdB2 were similarly immunogenic in mice, resulting in very similar Ab profiles with regard to Ig sub-class [10]. In that study, while long-term memory B-cell driven Ab recall responses were observed against TcdB1 and TcdB2, neutralization of TcdB2 and resistance to in vivo challenge with toxin was vastly inferior to that against TcdB1 [10]. This suggests that the memory B cell compartment could essentially be mis-directed against TcdB from some strains, resulting in high titers of non-neutralizing Ab.…”
Section: Vaccine Candidates and Constraints On Adaptive Immunity To Themmentioning
confidence: 99%
See 2 more Smart Citations